The Business School In The 21 st Century & Beyond: Integrating Knowledge Management Philosophy - McFarlane, Donovan A.; Mujtaba, Bahaudin G.; Cavico, Frank J. (Journal of Knowledge Management Practice, 2009)
This paper examines the business school in the 21st century with special emphasis on integrating Knowledge Management (KM) philosophy as an innovative platform in ensuring sustainability and survival. The authors propose the integration and use of knowledge management philosophy and concepts by means of the KMBOK (knowledge management body of knowledge) and exploration of market leadership models to create competitive programs and effective knowledge workers to deal with the problems and challenges of today and the future. The field of knowledge management and its applications and ideas are proposed as the next logical passage for rebuilding and developing business schools to their optimum.
Keywords: Knowledge management; Knowledge input; Integrated KM approach; KMBOK; Knowledge stocks